2006
DOI: 10.4067/s0301-732x2006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Características hematológicas y patológicas de cerdos inoculados experimentalmente con el aislado chileno del virus síndrome respiratorio y reproductivo porcino

Abstract: SUMMARYThe aims of this study were to characterize the haematological and bone marrow changes, gross and microscopic lesions of pigs experimentally inoculated with the Chilean isolate of porcine reproductive and respiratory syndrome virus. Twelve 3-week-old pigs were divided in 4 groups of 3, one of which corresponded to the negative control group sacrificed at 0 days post-inoculation (dpi), and the 3 remaining groups corresponded to the inoculated pigs sacrificed at 7, 14 and 21 dpi. For each sampling period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Because of the postulated notion that the outbreaks of PRRSV in Chile could involve certain PRRSV strains of unusual attenuation and limited dissemination (Ruiz et al., 2003), this study was designed to better understand how a typical Chilean isolate behaves from the point of view of its shedding and its capacity for transmission by direct contact as it might occur under field conditions. Previous experimental studies (Quezada et al., 2004; Ramírez et al., 2004, 2006) suggested that the Chilean PRRSV might behave differently from some of the other US isolates of greater pathogenicity, such as those described by Rossow et al. (1994, 1995), Halbur et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Because of the postulated notion that the outbreaks of PRRSV in Chile could involve certain PRRSV strains of unusual attenuation and limited dissemination (Ruiz et al., 2003), this study was designed to better understand how a typical Chilean isolate behaves from the point of view of its shedding and its capacity for transmission by direct contact as it might occur under field conditions. Previous experimental studies (Quezada et al., 2004; Ramírez et al., 2004, 2006) suggested that the Chilean PRRSV might behave differently from some of the other US isolates of greater pathogenicity, such as those described by Rossow et al. (1994, 1995), Halbur et al.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the postulated notion that the outbreaks of PRRSV in Chile could involve certain PRRSV strains of Nasal 0/5 3/5 4/5 4/5 4/5 4/5 0/5 0/5 1/5 1/5 Ocular 0/5 0/5 5/5 2/5 3/5 2/5 0/5 0/5 0/5 0/5 Saliva 0/5 0/5 0/5 4/5 2/5 4/5 2/5 2/5 1/5 2/5 Faeces 0/5 0/5 2/5 1/5 3/5 4/5 0/5 0/5 0/5 0/5 unusual attenuation and limited dissemination (Ruiz et al, 2003), this study was designed to better understand how a typical Chilean isolate behaves from the point of view of its shedding and its capacity for transmission by direct contact as it might occur under field conditions. Previous experimental studies (Quezada et al, 2004;Ramírez et al, 2004Ramírez et al, , 2006 suggested that the Chilean PRRSV might behave differently from some of the other US isolates of greater pathogenicity, such as those described by Rossow et al (1994Rossow et al ( , 1995, Halbur et al (1995Halbur et al ( , 1996b and Rossow et al (1999), with a shorter viraemia and a multisystemic viral distribution although with lesions of lesser intensity. In this study the pigs behaved similarly to previous studies, with only slight and non-specific symptoms being detected in the group of inoculated animals and in all the contact groups without the presence of evident respiratory symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation